The virulence of NDV NA-1 strain regulated by the 3′ leader or 5′ trailer sequences. (January 2019) - Gao, Chao; Ding, Zhuang; Qian, Jing; Liu, Xinxin; Zhang, Xiaodong; Cong, Yanlong; Ding, Chan; Yu, Shenqing; Hu, Shunlin; Liu, Xiufan; Stoeger, Tobias; Yin, Renfu
Abstract: The 3′ and 5′ terminal regions of Newcastle disease virus (NDV) genome are cis-acting regulatory elements involved in replication, transcription, and packaging of genomic and anti-genomic viral RNA. There are 6 different nucleotides (nts) at the 3′ and 34 different nts at the 5′ end of genome in the velogenic NA-1 strain and lentogenic LaSota strain, sharing 90.00% and 70.18% identity, respectively. We investigated the roles of 3′ and 5′ terminus in the NA-1 strain in viral replication, virulence and pathogenicity. Three NA-1 strain-based recombinant viruses (rNA-L, rNA-T, and rNA-LT) were generated using reverse genetics by either replacing the 3′ leader or 5′ trailer sequence of NA-1 strain or both with the corresponding sequences of the LaSota strain. Viral replication kinetics and pathogenicity of rNA-L and rNA-T were indistinguishable to that of the parental NA-1 strain, demonstrating that individual replacement or 3′ or 5′ terminal sequences had little influence. However, the synchronal replacement of both 3′ and 5′ terminal sequences resulted in decreased viral plaque size, reduced virulence and weaker pathogenicity in 2-week-old chickens. Therefore, our results suggest that the 3′ and 5' terminal sequences of NDV genome could only influence the viral virulence when worked collaboratively, while separate replacement would not alter its biological characteristics. Highlights: Three recombinant viruses were generated by replacing the 3′ and 5′ terminal sequences of virulent NA-1 strain with corresponding sequences from the lentogenic LaSota strain. The replacement of the 3′ and 5′ terminal sequences was associated with mild or moderate disease. The individual replacement of the 3′ or 5′ terminal sequences had no effect on viral virulence. The terminal sequences of heterogenic strains play a significant role in the virulence of the NA-1 strain.